2016
DOI: 10.3399/bjgp16x684397
|View full text |Cite
|
Sign up to set email alerts
|

Safety of community-based minor surgery performed by GPs: an audit in different settings

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 10 publications
3
34
0
Order By: Relevance
“…In studies from both the UK [11] and Ireland [12], the outcomes for primary excision of malignant melanoma were shown to be equivalent between GP and hospital providers. A community-based surgery audit from the UK, which examined 6138 procedures, concluded that GP minor surgery was safe and prompt and that GPs working within a managed framework performed better than less well-supported GPs [13].…”
Section: Introductionmentioning
confidence: 99%
“…In studies from both the UK [11] and Ireland [12], the outcomes for primary excision of malignant melanoma were shown to be equivalent between GP and hospital providers. A community-based surgery audit from the UK, which examined 6138 procedures, concluded that GP minor surgery was safe and prompt and that GPs working within a managed framework performed better than less well-supported GPs [13].…”
Section: Introductionmentioning
confidence: 99%
“…In a self-reported study from volunteer GPs doing local anaesthetic skin lesion excisions, 5 6138 procedures were analysed, of which 926 were confirmed as malignancies, including 722 BCCs. Model 2 GPs and GPwSIs had statistically significantly higher rates of complete excision than ESGPs.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited evidence assessing specifically whether GPs with a degree of skin surgery specialism or frequency of practice have superior excision performance. Furthermore, although secondary care may have superior excision rates, suggesting that this is the optimal location for skin cancer management, this does not take into consideration patient preference . Were specific characteristics predictive of improved GP surgical performance to be identified, these might be used to guide policy development and improve the care of patients with NMSC.…”
mentioning
confidence: 99%